Ribosomal protein S6 is hyperactivated and differentially phosphorylated in epidermal lesions of patients with psoriasis and atopic dermatitis. (9th November 2014) - Ruf, M.T.; Andreoli, A.; Itin, P.; Pluschke, G.; Schmid, P.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Phosphorylation of ribosomal protein S6 is important for the initiation of translation. S6 becomes phosphorylated via the mammalian target of rapamycin pathway, which is activated in psoriatic skin. What does this study add? In psoriasis and atopic dermatitis, S6 phosphorylation is associated with inflammation and epidermal hyperproliferation. S6 is differentially phosphorylated in distinct layers of the diseased epidermis, which may impact on the proliferation/differentiation of keratinocytes.